Social transformation of winongo river bank people in managing domestic waste - Zunariyah Siti; Sunesti Yuyun; Demartoto Argyo (E3S Web of Conferences)
Social transformation in managing household waste is a collective commitment to reduce the impact of climate change and realize sustainable development goals. The article aims to explain the process of social transformation in managing domestic waste and the factors that affect it. The research location is in the Winongo riverbank area of Yogyakarta through a qualitative exploration approach. As a result, the social transformation process runs through the stages of capacity building, group empowerment, relational community development, and new cultural development. The four stages do not run linearly, but tend to be dynamic and adaptive. The capacity building stage is very important because it is related to the internalization of new values on waste and its implications for the environment and health. Social transformation occurs if economic and political empowerment capital can be built to form a new culture. The factors inhibiting the transformation process are changes in the formation of actors and gender bias in domestic waste management. It takes a reorientation of the institutional format based on social capital and innovation of household waste management strategies with economic and ecological value to reduce the impact of climate change.